A poetic inquiry into an EFL learner’s identity and study abroad experience in a non-English speaking country - Amalina, Nur; Musthafa, Bachrudin (Jurnal Penelitian Pendidikan, 2021)
This qualitative case study investigates the way an EFL student reflects on her identity and study abroad experience through a series of pantuns, a four-lined rhyming Indonesian poem. This study conducts a poetic identity analysis on ten English pantuns written by a Ukrainian student who studied English education in Indonesia. The poems were analyzed in terms of their context, content, and stylistic choices. The study unveils that through the ten pantuns, the participant voiced the sociocultural and racial issues she faced as an international student in a non-English speaking country, contemplating her membership in local and global communities, expressing the sense of camaraderie she felt with Indonesian EFL learners and with multicultural community, and constructing new identity in the third space. Further, she recounted her pantun writing experience as challenging due to the genre’s economic word count and rhyming scheme, but satisfying because writing pantun brings her closer to a form of Indonesian literature, and its culture by extension. In pantun’s prefatory section, the participant set the tone of the poem and drew metaphors of her personal and emotional insight, whereas in the following content section, she wrote rhyming lines while expressing said insights. Thus, this study illustrates how writing pantun helps a language learner exercise her linguistic and literary awareness while also enable her to explore her memories, emotion and perception. Pedagogical implication is also presented in this study.